Contemporary Black biography. profiles from the international Black community. Volume 70. - Gale Group (Detroit, Michigan Gale, 2009)
Biographical profiles of important and influential persons of African heritage who form the international black community. Covers persons of various nationalities in a wide variety of fields providing coverage of names found in today's headlines as well as selected individuals from earlier in this century whose influence continues to have an impact on contemporary life.
Sani Abacha -- Moshood Abiola -- Uwem Akpan -- Karen Bass -- Kathleen Battle -- Beyonc{caron} -- Edward Boyd -- Donna Brazile -- George Butler Jr. -- Louis Butler --Cee-Lo -- Alice Coltrane -- Edward E. Cornwell III -- Chaka Fattah -- Laurence Fishburne -- Harold E. Ford Jr. -- Johnny Ford -- Bernardin Gantin -- Kevin Garnett -- Haile Gebrselassie -- Sylvia Harris -- Shannon Holmes -- Tom Jackson -- Benjamin Jealous -- Micha{llig}lle Jean -- Kevin Johnson -- Van Jones -- Eddie Levert -- Ramsey Lewis -- Marcus Mabry -- Julianne Malveaux -- Rita Marley -- Crystal McCrary Anthony -- James Alan McPherson -- Walter Dean Myers -- Katoucha Niane -- Star Parker -- Pinetop Perkins -- Wayne Rhoden -- Sidney Ribeau -- Darryl Roberts -- Jimmy Rollins -- Anika Noni Rose -- Jimmy Slyde -- Kemba Smith -- Marie F. Smith -- Cecil Taylor -- Jason Taylor -- Viola Vaughn -- Gelsy Verna -- Thomas Weeks III -- Clarence Williams -- Russell Williams II -- Rayfield Wright.
"ISSN 1058-1316".
Includes bibliographical references and index.
Electronic reproduction.
Keywords: African Americans -- Biography; Blacks -- Biography; African American leadership; African American athletes; Athletes, Black; African American artists; Artists, Black; African American businesspeople; Businesspeople, Black; African American politicians; African American religious leaders; African American authors; Authors, Black; African American musicians; Musicians, Black; African American actors; Actors, Black; Electronic books